2015 IEEE International Solid-State Circuits Conference - (ISSCC) Digest of Technical Papers 2015
DOI: 10.1109/isscc.2015.7063100
|View full text |Cite
|
Sign up to set email alerts
|

22.6 A 25Gb/s 4.4V-swing AC-coupled Si-photonic microring transmitter with 2-tap asymmetric FFE and dynamic thermal tuning in 65nm CMOS

Abstract: Silicon photonic microring modulators (MRMs) offer a promising approach for realizing energy-efficient wavelength-division multiplexing (WDM) optical interconnects. For data-rates greater than 10Gb/s, depletion-mode MRMs are generally preferred over their injection-mode counterparts due to their shorter carrier lifetimes and resulting higher bandwidths. Unfortunately, these depletion-mode MRMs typically exhibit low PN junction tunability, thereby requiring higher modulation voltages in order to provide >6dB ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…After separating the modulated optical signals based on their wavelengths, PDs are used to detect each of the incoming signals. It has already been shown that MRR-based links are capable of operating at an excess of 25 Gb/s per wavelength [30], [53], [54], implying that a 25 Gb/s lane could be replicated as many times as needed to reach the aggregate goal. To relax the RX front-end design requirements to attain a 100 Gb/s throughput and beyond, the multiplexing factor (number of wavelengths, n) can theoretically be increased to a large extent [3].…”
Section: Towards a Power Efficient Tera-bit/s Linkmentioning
confidence: 99%
“…After separating the modulated optical signals based on their wavelengths, PDs are used to detect each of the incoming signals. It has already been shown that MRR-based links are capable of operating at an excess of 25 Gb/s per wavelength [30], [53], [54], implying that a 25 Gb/s lane could be replicated as many times as needed to reach the aggregate goal. To relax the RX front-end design requirements to attain a 100 Gb/s throughput and beyond, the multiplexing factor (number of wavelengths, n) can theoretically be increased to a large extent [3].…”
Section: Towards a Power Efficient Tera-bit/s Linkmentioning
confidence: 99%
“…Fig. 2(a) shows a differential cascode modulator driver capable of outputting NRZ modulation with 4.8Vpp-diff swing when implemented in a 1.2V 65nm CMOS technology [6]. At each side of the differential driver is a cascode output stage powered by a supply that is twice the nominal CMOS supply, allowing a 2.4V swing per modulator terminal in the 65nm node without transistor overstress.…”
Section: A Transmitter Driversmentioning
confidence: 99%
“…Ring modulator transmission curves are shown in Fig. 5, with a maximum 4.4Vpp-diff swing considered due to the capacitive voltage division associated with the AC-coupling that maintains reverse-bias operation [6]. The total modulator nonlinearity due to the voltage-to-index and index-to-intensity responses must be considered for uniform PAM4 level spacing, with the input laser wavelength optimized separately for the single and two-segment devices.…”
Section: B Carrier-depletion Ring Modulatorsmentioning
confidence: 99%
“…At data rates near 10 Gb/s, injection-mode modulators based on forward-biased p-i-n junctions are an attractive device due to their high modulation depths and rapid bias-based resonance wavelength tuning capabilities [6,7], but their speed with simple non-return-to-zero (NRZ) modulation is limited by both long minority carrier lifetimes and series resistance effects [8]. Depletion-mode modulators based on reverse-biased p-n junctions can achieve high speed (~40 Gb/s) [9], but require large drive voltages [10]. Injection-mode modulators provide higher energy efficiency and depletion-mode modulators offer higher bandwidth density.…”
Section: Introductionmentioning
confidence: 99%